ANALISIS PENGARUH PROFIL SUDUH TERHADAP DAYA TURBIN VORTEX - Marfizal, Marfizal; Sufiyanto, Sufiyanto; Wardianto, Dedi (ITP Press, 2023)
A vortex turbine is a turbine that operates by utilizing a vortex flow as a drive for turbine blades which then the turbine shaft is connected to a generator to convert shaft mechanical energy into the form of electrical energy. In this study a test will be carried out on a vortex turbine with a head of 1 m, a flow rate of 0.12 m3/s. In the testing process, 3 types of blades will be used, namely straight blades, curved blades and finned curved blades. After testing, it can be concluded that the highest power is found in the curved blade of 959.08 Watt and then the finned curved blade is 714.38 Watt, while the lowest power is found in the straight blade type of 582.48 Watt. The resulting rotation can be seen in the graph below. The highest rotation is found in the finned curved blade of 540.00 rpm and the next is the curved blade of 517.67 rpm, while the lowest rotation is found in the straight blade type of 510.67 rpm. For the efficiency of each metal blade, it can be seen that curved blades are still the highest followed by curved blades with finned blades, the lowest being straight blades with salty blade efficiencies of 98%, 73% and 59%